Enchancing Employee Performance: The Roles of Motivation and Work Discipline - Susan Ridwan; Jusdijachlan (Greenation International Journal of Economics and Accounting, 2023)
The goal of this study was to examine the simultaneous and partial effects of competence, motivation, and work discipline on employee performance at Room Division V Hotel Bandung. Utilizing a Likert scale with ordinal measurement, descriptive and verification analysis is the study methodology used. The Product Moment Correlation technique from Pearson, with a saturated sample design of 35 respondents, tests the applicability's validity and dependability. In contrast, the data analysis technique makes use of statistical data analysis and a formula for path analysis. The Successive Interval Method is used to convert the data from the ordinal scale to the interval scale. According to the findings of the hypothesis test, 59.5% of the variance in employee performance is explained by factors other than competence, motivation, and work discipline, while the remaining 40.5% is affected by other factors. According to partial testing, work motivation had a substantial impact on employee performance with a 25.5% effect, competence did not have a significant impact, and work discipline had a big and positive 51.5% impact.